1995
DOI: 10.1042/bj3090299
|View full text |Cite
|
Sign up to set email alerts
|

Binding of gelatinases A and B to type-I collagen and other matrix components

Abstract: Matrix sequestration of matrix metalloproteinases may be important for the facilitation of remodelling events and the migration of cells through the extracellular matrix. Using an ELISA technique we studied the ability of pro and active forms of gelatinases A and B (GLA and GLB) to bind to matrix components and the contribution made by the different enzyme domains. Pro and active forms of GLA and GLB bound to type-I and type-IV collagens, gelatin and laminin films. Binding to collagens occurred exclusively via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
185
0
13

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(205 citation statements)
references
References 49 publications
7
185
0
13
Order By: Relevance
“…Indeed, in agreement with our observations (Fig. 3), Allan and co-workers [69] demonstrated that both pro-and active MMP-2 efficiently bind to thin coats of type I and type IV collagens, but very poorly to fibronectin. This collagen-binding property is solely mediated by the fi-bronectin-type II inserts present in the catalytic domain of the enzyme [69].…”
Section: Mmp-2 Activation By Type Tv Collagen: a Hypothetical Mechanismsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, in agreement with our observations (Fig. 3), Allan and co-workers [69] demonstrated that both pro-and active MMP-2 efficiently bind to thin coats of type I and type IV collagens, but very poorly to fibronectin. This collagen-binding property is solely mediated by the fi-bronectin-type II inserts present in the catalytic domain of the enzyme [69].…”
Section: Mmp-2 Activation By Type Tv Collagen: a Hypothetical Mechanismsupporting
confidence: 93%
“…3), Allan and co-workers [69] demonstrated that both pro-and active MMP-2 efficiently bind to thin coats of type I and type IV collagens, but very poorly to fibronectin. This collagen-binding property is solely mediated by the fi-bronectin-type II inserts present in the catalytic domain of the enzyme [69]. As a consequence, the interaction of cell surface anchored MMP-2 with the molecules of type IV collagen is likely to induce the clustering of the MT1-MMP/TIMP-2/MMP-2 ternary complexes at the sites of interaction with the ECM, therefore promoting the intermolecular autocatalytic cleavage required to generate fully mature MMP-2.…”
Section: Mmp-2 Activation By Type Tv Collagen: a Hypothetical Mechanismmentioning
confidence: 99%
“…It is also possible that the interaction of NCl with MMP-2 or MMP-3 might be weakened or abolished by the interaction of gelatin or transferrin substrates with the enzymes. Complex interactions of NCl have been reported with gelatin and other matrix components (Allan et al, 1995). Inhibition of both MMP-2 and MMP-3 in peptide assays argues against an involvement of the fibronectin-like domains which are unique to MMP-2.…”
Section: Discussionmentioning
confidence: 97%
“…However, the susceptibility of these matrix-bound MMPs to inhibition were not examined in these studies. It is noteworthy in this respect that immunolocalization studies have demonstrated that MMP-2, MMP-9, MMP-3, and MMP-1 bind to matrix components in rapidly resorbing tissues in vivo [127], and it has been postulated that matrix binding of MMPs may confer retention, stability, and bioactivity for prolonged periods, thus facilitating their roles in pericellular proteolysis [125].…”
Section: Metalloproteinasesmentioning
confidence: 99%
“…Both gelatinases (MMP-2 and MMP-9) have been shown to bind to type I and IV collagen, gelatin, and fibronectin via their amino-terminal domains [125]. Collagenase (MMP-1) and stromelysin (MMP-3) bind through their carboxy-terminal domains to collagen fibrils in vitro [126].…”
Section: Metalloproteinasesmentioning
confidence: 99%